Pengaruh Harga, Kualitas Produk, dan Citra Merek Terhadap Keputusan Pembelian Beras Anak Daro di Kecamatan Dumai Timur - Dasya Fitriana Putri; Shorea Khaswarina; Fanny Septya (Jurnal MeA (Media Agribisnis), 2022)
The diversity of branded local rice supply in the market will have an impact on competitionOne of the ways that Anak Daro rice producers do to face the competition is to improve product quality, which will create an attraction for consumers to make purchasing decisions.It is important to study the effect of price, product quality, and brand image on purchasing decisions as a consideration for the rice agro-industry to improve the attributes attached to packaged rice. The purpose of this study was to determine the effect of price, product quality, and brand image simultaneously and partially on the purchasing decision of Anak Daro rice in Dumai Timur District. This research data collection technique used a questionnaire that has been tested for validity and reliability. The statistical analysis method was multiple linear regression, and it has been analyzed by using SPSS software. In this study, 73 respondents were selected using the proportional random sampling method. The results of this study indicate that the variables of price (X1), product quality (X2), and brand image (X3) have a positive and significant effect on purchasing decisions for Anak Daro rice in East Dumai District.